Two modes of O-H center dot center dot center dot O hydrogen bonding utilized in dimorphs of racemic 6-O-acryloyl-2-O-benzoyl-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
The title compound, C(17)H(16)O(8), yields conformational dimorphs [forms (I) and (II)] at room temperature, separately or concomitantly, depending on the solvent of crystallization. The yield of crystals of form (I) is always much more than that of crystals of form (II). The molecule has one donor -OH group that can make intermolecular O-H center dot center dot center dot O hydrogen bonds with one of the two acceptor C O groups, as well as with the hydroxyl O atom; interestingly, each of the options is utilized separately in the dimorphs. The crystal structure of form (I) contains one molecule in the asymmetric unit and is organized as a planar sheet of centrosymmetric dimers via O H center dot center dot center dot O hydrogen bonds involving the OH group and the carbonyl O atom of the acryloyl group. In the crystal structure of form (II), which contains two independent molecules in the asymmetric unit, two different O-H center dot center dot center dot O hydrogen bonds, viz. hydroxyl-hydroxyl and hydroxyl-carbonyl (benzoyl), connect the molecules in a layered arrangement. Another notable feature is the transformation of form (II) to form (I) via melt crystallization upon heating to 411 K. The higher yield of form (I) during crystallization and the thermal transition of form (II) to form (I) suggest that the association in form (I) is more highly favoured than that in form (II), which is valuable in understanding the priorities of molecular aggregation during nucleation of various polymorphs.